2017
DOI: 10.1038/hdy.2017.50
|View full text |Cite
|
Sign up to set email alerts
|

Heritable gene expression differences between lake and stream stickleback include both parallel and antiparallel components

Abstract: The repeated phenotypic patterns that characterize populations undergoing parallel evolution provide support for a deterministic role of adaptation by natural selection. Determining the level of parallelism also at the genetic level is thus central to our understanding of how natural selection works. Many studies have looked for repeated genomic patterns in natural populations, but work on gene expression is less common. The studies that have examined gene expression have found some support for parallelism, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 117 publications
0
28
0
Order By: Relevance
“…Transcriptomic studies have been particularly helpful in understanding processes involved in adaptive phenotypic divergence of postglacial fishes (Kitano et al, 2011;Hanson et al, 2017) where, for example, genes in bone morphogenetic protein and calcium signalling pathways are involved in the coordinated evolution of traits involved in the divergence of lake whitefish morphs . Such functional approaches are used far less in the context of understanding Studies on developmental architecture consider genotype/phenotype relationships that can occur across a range of environments (E1 in red and E2 in blue) and at various stages of ontogeny.…”
Section: (1) Phenotypic Variation Results From Complex Genetic and Enmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptomic studies have been particularly helpful in understanding processes involved in adaptive phenotypic divergence of postglacial fishes (Kitano et al, 2011;Hanson et al, 2017) where, for example, genes in bone morphogenetic protein and calcium signalling pathways are involved in the coordinated evolution of traits involved in the divergence of lake whitefish morphs . Such functional approaches are used far less in the context of understanding Studies on developmental architecture consider genotype/phenotype relationships that can occur across a range of environments (E1 in red and E2 in blue) and at various stages of ontogeny.…”
Section: (1) Phenotypic Variation Results From Complex Genetic and Enmentioning
confidence: 99%
“…Transcriptomic studies have been particularly helpful in understanding processes involved in adaptive phenotypic divergence of postglacial fishes (Kitano et al ., ; Hanson et al ., ) where, for example, genes in bone morphogenetic protein and calcium signalling pathways are involved in the coordinated evolution of traits involved in the divergence of lake whitefish morphs (Filteau et al ., ). Such functional approaches are used far less in the context of understanding developmental variation (but see Ahi et al ., , ) even though they could provide a direct link between environmental cues and the developmental response, as well as inform us on eco‐evolutionary feedback loops (Becks et al ., ).…”
Section: From the Inside Looking Out: Intrinsic Factors And Leveraginmentioning
confidence: 97%
“…The transcriptome analysis of dental tissues in marine and freshwater populations showed parallel transcriptome evolution (Hart et al., ). In contrast, another study on the livers of lake–stream sticklebacks showed not only parallel patterns, but also antiparallel patterns (Hanson et al., ). Further tests of transcriptome parallelism using different stickleback systems are, therefore, essential for a better understanding of the prevalence and mechanisms of the parallel evolution of transcriptome.…”
Section: Introductionmentioning
confidence: 92%
“…Consistent with this prediction, some of the previous transcriptome studies showed parallel transcriptome evolution between the low-and the high-latitude populations of Drosophila melanogaster and D. simulans and between the marine and freshwater ecotypes of stickleback (Hart, Ellis, Eisen, & Miller, 2018;Zhao, Wit, Svetec, & Begun, 2015). However, other studies failed to show significant parallel patterns between the wild and weedy populations of Helianthus annuus (Lai, Kane, Zou, & Rieseberg, 2008) or revealed not only parallel, but also antiparallel patterns (i.e., ecotypes in different lineages showed opposite direction of differential expression) between the normal and dwarf morphs of whitefish (Derome, Duchesne, & Bernatchez, 2006) and between the lake and stream ecotypes of stickleback (Hanson, Hu, Hendry, & Barrett, 2017). Further analysis on different systems is, therefore, essential for a better understanding of the prevalence of parallelism in transcriptome evolution.…”
mentioning
confidence: 99%
“…The phenotypes of characterizing these antagonistic interactions may appear similar, but the underlying molecular mechanism may differ substantially. Conversely, seemingly different phenotypic trajectories may also be based on the same molecular machinery that merely differs in its expression levels (Elmer et al., ; Hanson, Hu, Hendry, & Barrett, ). Overall, our mechanistic understanding, and consequently also our understanding of the mode and speed of co‐evolution, is so far limited.…”
Section: Introductionmentioning
confidence: 99%